Adaptasi Pelaku Transgender Di Kecamatan Manggala Kota Makassar - R, Herdianty (Universitas Negeri Makassar, 2018)
Therfor, the study aims at examining (i) the factors which cause transgender has deviant behavior, (ii) the adaptation process of transgender in Makassar city, (iii) the adaptation pattern of organized transgender that has potential in social reproduction. The type of this study is qualitative research with descriptive. The site of the study was in Manggala subdistrict of Makassar city. The informants of the study consisted of transgender, parents of transgender, public, and government with the total of 10 people. Data was collected by employing interview, observation, and documentation. Data was analyzed by conduction data reduction, data presentation, and verivication or conclusion. The result of the study indicates that the adaptation of transgender in Makassar city of Manggala subdistrict is through occupation or their profession. They cover their deviant behavior and the society can accept their existence.